Mitigative potential of kaempferide against polyethylene microplastics induced testicular damage by activating Nrf-2/Keap-1 pathway - Muhammad Umar Ijaz; Zainab Rafi; Ali Hamza; Amany A. Sayed; Ghadeer M. Albadrani; Muath Q. Al-Ghadi; Mohamed M. Abdel-Daim (Ecotoxicology and Environmental Safety, 2024)
Polyethylene microplastics (PE-MPs) are one of the environmental contaminants that instigate oxidative stress (OS) in various organs of the body, including testes. Kaempferide (KFD) is a plant-derived natural flavonol with potential neuroprotective, hepatoprotective, anti-cancer, anti-oxidant and anti-inflammatory properties. Therefore, the present study was designed to evaluate the alleviative effects of KFD against PE-MPs-prompted testicular toxicity in rats. Fourty eight adult male albino rats were randomly distributed into 4 groups: control, PE-MPs-administered (1.5 mgkg-1), PE-MPs (1.5 mgkg-1) + KFD (20 mgkg-1) co-treated and KFD (20 mgkg-1) only treated group. PE-MPs intoxication significantly (P < 0.05) lowered the expression of Nrf-2 and anti-oxidant enzymes, while increasing the expression of Keap-1. The activities of anti-oxidants i.e., catalase (CAT), glutathione reductase (GSR), superoxide dismutase (SOD), hemeoxygene-1 (HO-1) and glutathione peroxidase (GPx) were reduced, besides malondialdehyde (MDA) and reactive oxygen species (ROS) contents were increased significantly (P < 0.05) following the PE-MPs exposure. Moreover, PE-MPs exposure significantly (P < 0.05) reduced the sperm motility, viability and count, whereas considerably (P < 0.05) increased the dead sperm number and sperm structural anomalies. Furthermore, PE-MPs remarkably (P < 0.05) decreased steroidogenic enzymes and Bcl-2 expression, while increasing the expression of Caspase-3 and Bax. PE-MPs exposure significantly (P < 0.05) reduced the levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH) and testosterone, whereas inflammatory indices were increased. PE-MPs exposure also induced significant histopathological damages in the testes. Nevertheless, KFD supplementation significantly (P < 0.05) abrogated all the damages induced by PE-MPs. The findings of our study demonstrated that KFD could significantly attenuate PE-MPs-instigated OS and testicular toxicity, due to its anti-oxidant, anti-inflammatory, androgenic and anti-apoptotic potential.